2008
DOI: 10.1186/cc7010
|View full text |Cite
|
Sign up to set email alerts
|

Pressure support ventilation attenuates ventilator-induced protein modifications in the diaphragm

Abstract: Introduction Controlled mechanical ventilation (CMV) induces profound modifications of diaphragm protein metabolism, including muscle atrophy and severe ventilator-induced diaphragmatic dysfunction. Diaphragmatic modifications could be decreased by spontaneous breathing. We hypothesized that mechanical ventilation in pressure support ventilation (PSV), which preserves diaphragm muscle activity, would limit diaphragmatic protein catabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 60 publications
0
97
0
10
Order By: Relevance
“…Only one investigation has explored the influence of partial support MV on rat diaphragm protein synthesis. This study reveals that compared with spontaneous breathing animals, partial support ventilation does not promote a significant decrease in diaphragm protein synthesis in vitro (32). How much ventilator support was provided in this study is unknown and whether or not these results can be replicated in vivo remains unclear and warrants additional work.…”
Section: Mv-induced Decreases In Protein Diaphragmatic Synthesismentioning
confidence: 76%
See 2 more Smart Citations
“…Only one investigation has explored the influence of partial support MV on rat diaphragm protein synthesis. This study reveals that compared with spontaneous breathing animals, partial support ventilation does not promote a significant decrease in diaphragm protein synthesis in vitro (32). How much ventilator support was provided in this study is unknown and whether or not these results can be replicated in vivo remains unclear and warrants additional work.…”
Section: Mv-induced Decreases In Protein Diaphragmatic Synthesismentioning
confidence: 76%
“…Specifically, Futier et al (32) reported that 18 h of partial support MV did not increase proteolysis in the rat diaphragm. In contrast, Hudson et al demonstrated that 18 h of partial support MV activates the 20S proteasome, calpain, and caspase-3 in the diaphragm (44).…”
Section: Mv-induced Proteolysis In the Diaphragmmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbiturates and neuromuscular blockers have deleterious effects in skeletal muscle function 29 . When applied on an intermittent manner, nevertheless, they do not contribute to VIDD 28 .…”
Section: Analysis Of Experimental Designmentioning
confidence: 88%
“…It is also well-recognized in some pediatric situations 27 . Pressure support ventilation (PSV) was chosen because literature has only one study investigating the attenuation of protein catabolic effects by using this ventilation mode 28 . This study analyzes diaphragmatic muscle atrophy and the PSV mode seems to preserve diaphragmatic muscle activity when compared with the CMV mode.…”
Section: Analysis Of Experimental Designmentioning
confidence: 99%